2006
DOI: 10.1109/icdm.2006.138
|View full text |Cite
|
Sign up to set email alerts
|

SAXually Explicit Images: Finding Unusual Shapes

Abstract: Among the visual features of multimedia content, shape is of particular interest because humans can often recognize objects solely on the basis of shape. Over the past three decades, there has been a great deal of research on shape analysis, focusing mostly on shape indexing, clustering, and classification. In this work, we introduce the new problem of finding shape discords, the most unusual shapes in a collection. We motivate the problem by considering the utility of shape discords in diverse domains includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…Note that once the new breakpoints are defined, and Tables 3 and 4 are appropriately adjusted, the lower bounding property still holds. Finally, in an interesting new development, Wei et al (2006) have shown techniques to adapt SAX to various problems in 2D shape matching, after modifying algorithms/representations to allow for rotation invariance, which in the SAX representation corresponds to circular shifts.…”
Section: Extensions To Saxmentioning
confidence: 99%
“…Note that once the new breakpoints are defined, and Tables 3 and 4 are appropriately adjusted, the lower bounding property still holds. Finally, in an interesting new development, Wei et al (2006) have shown techniques to adapt SAX to various problems in 2D shape matching, after modifying algorithms/representations to allow for rotation invariance, which in the SAX representation corresponds to circular shifts.…”
Section: Extensions To Saxmentioning
confidence: 99%
“…Wei et al's rotation-invariant discord discovery technique, which we refer to as RI-DISCORD (Wei et al 2006), is an anomaly detection methods that discovers global anomalies or discords in shape data. Discords, whose definition is reminiscent of the distancebased outlier definition, are the m most anomalous time series (or subregions if the input is a single time series) with the farthest nearest neighbors .…”
Section: Time Series Methods For Unphased Datamentioning
confidence: 99%
“…There are other versions and extensions of SAX [11], [25], [26], [28]. These versions use it for other applications or apply it to index massive datasets, or compute MINDIST differently [18].…”
Section: The Symbolic Aggregate Approximation (Sax)mentioning
confidence: 99%